2019
DOI: 10.1159/000500503
|View full text |Cite
|
Sign up to set email alerts
|

Transurethral Resection for the Treatment of an Inflammatory Myofibroblastic Tumor of the Urinary Bladder: A Case Report

Abstract: Inflammatory myofibroblastic tumors (IMT) of the urinary bladder is a remarkably rare bladder tumor. To this day, no standardized treatment protocol has been recognized. Here we report a case of bladder IMT in a 14-year-old girl presenting with urgency, frequency, and gross painless hematuria for a week. Complete excision of the bladder IMT was amenable with transurethral resection of bladder tumor (TURBT). Follow-up cystoscopy did not detect any recurrence. Minimally invasive bladder-sparing treatments are a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…A systematic review by Teoh et al [3] in 2014 evaluated 182 cases of urinary bladder IMT in the literature [3]. Another review of the literature by Song et al in 2019 revealed 16 additional patients, for a total of 198 cases of urinary bladder IMT to date [3]. In children, the literature review by Houben et al [8] identified 35 cases of IMT of the bladder in children [3].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A systematic review by Teoh et al [3] in 2014 evaluated 182 cases of urinary bladder IMT in the literature [3]. Another review of the literature by Song et al in 2019 revealed 16 additional patients, for a total of 198 cases of urinary bladder IMT to date [3]. In children, the literature review by Houben et al [8] identified 35 cases of IMT of the bladder in children [3].…”
Section: Discussionmentioning
confidence: 99%
“…Another review of the literature by Song et al in 2019 revealed 16 additional patients, for a total of 198 cases of urinary bladder IMT to date [3]. In children, the literature review by Houben et al [8] identified 35 cases of IMT of the bladder in children [3]. Of these 35 patients, 20 were girls, and the median age was 7 years (range 2-16) [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations